FATAL INJURY IN THE AGEING WORKFORCE. (7th October 2012) - Ozanne-Smith, J; Jones, C; Watson, W; Kitching, F
Abstract : Background: Australia's workforce is ageing due to demographic and economic factors. Aims: (1) To describe the dimensions, nature, and external causes of fatalities in workers aged 55 years and older, Australia, 2000–2009. (2) To provide baseline data for future studies. (3) To investigate the preparedness of high risk industries and workers for the safety of the ageing workforce. Methods: Retrospective descriptive cohort data for workers aged 55 years and older (2000–2009) were extracted from population-based mortality data and analysed by age, gender, industry, occupation, and external cause. Subsequent studies investigated the preparedness of industry (stakeholder interviews) and workers (focus groups) for ageing workforce safety in the agriculture, transport and construction industries. Results: Of 2283 unintentional work-related fatalities: 336 were aged 55 years or older; 218 were 55–64; 83 were 65–74; 35 were 75 years or older; and 96.3% male. Industries with the most deaths among older workers were agriculture (37.8%), transport (19.3%) and construction (16.6%). Common themes among industry stakeholders included: awareness of the ageing workforce, the impact of ongoing heavy physical labour, and related management issues; an assumption that general safety initiatives will adequately cover older worker safety; and concerns about older worker compensation liabilities. The focus group study is in progress and results will be reported. Significance: Older worker deaths are a significant problem which will likely grow with workforce ageing. Employers and work authorities will need to consider the specific characteristics and vulnerabilities of older workers to enable implementation of appropriate injury prevention strategies for this population.